Praktik Perataan Laba dan Faktor - Faktor yang Mempengaruhinya - Pinatih, Ni Made Ayu; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 30 No 11 (2020), 2020)
The purpose of this study is to obtain empirical evidence of the influence of company size, profitability, financial leverage, and cash holding on income smoothing practices. The population in this study were 126 manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. The method of determining samples by purposive sampling. The number of samples obtained was 48 samples with observations over 5 years so there were 240 observations. The practice of income smoothing is calculated using the eckel index and the analysis technique used is logistic regression analysis. The results of the analysis in this study indicate that company size, profitability, financial leverage, and cash holding have a positive effect on the income smoothing practices of manufacturing companies listed on the Indonesia Stock Exchange for the period 2014 to 2018. This study can provide additional knowledge about the effect of company size, profitability, financial leverage and cash holding on income smoothing practices. Keywords : Company Size; Profitability; Financial Leverage; Cash holding; Income Smoothing.